Hydrodynamic Red Blood Cells Deformation by Quantitative Phase Microscopy and Zernike Polynomials - Memmolo, Pasquale; Miccio, Lisa; Merola, Francesco; Mugnano, Martina; Ferraro, Pietro (Frontiers in Physics, 2019)
RBCs elasticity is an important parameter for evaluating their health. Many studies have been performed for testing erythrocyte’s membrane stiffness under external stimuli, by means of the most diverse techniques. Here we exploit hydrodynamic deformation of RBCs in microfluidic channels to quantify the membrane shape variations through quantitative phase imaging by digital holography. In particular, two main processing have been employed, i.e. the morphology analysis based on quantitative phase variations and a new way to monitor the entire cell’s deformation, based on the modeling of RBCs as micro-lenses array. In fact, taking advantage of the RBC lens behavior, it is possible to correlate optical aberrations generated by the mechanical deformation to the entire membrane deformation itself, through a numerical analysis based on Zernike polynomials. We demonstrate that new optical parameters of RBCs can be measured and analyzed thus opening the route to exploit the bio-lensing modeling as a new biomechanical marker of RBCs.